Characteristics of Hemodynamic Disorders in Patients with Severe Traumatic Brain Injury - Ryta E. Rzheutskaya (Critical Care Research and Practice)
Purpose. To define specific features of central hemodynamic parameter changes in patients with isolated severe traumatic brain injury (STBI) and in patients with clinically established brain death and to determine the required course of treatment for their correction. Data and Research Methods. A close study of central hemodynamic parameters was undertaken. The study involved 13 patients with isolated STBI (group STBI) and 15 patients with isolated STBI and clinically established brain death (group STBI-BD). The parameters of central hemodynamics were researched applying transpulmonary thermodilution. Results. In the present study, various types of hemodynamic reaction (normodynamic, hyperdynamic, and hypodynamic) were identified in patients with isolated STBI in an acute period of traumatic disease. Hyperdynamic type of blood circulation was not observed in patients with isolated STBI and clinically established brain death. Detected hemodynamic disorders led to the correction of the ongoing therapy under the control of central hemodynamic parameters. Conclusions. Monitoring of parameters of central hemodynamics allows to detect the cause of disorders, to timely carry out the required correction, and to coordinate infusion, inotropic, and vasopressor therapy.